The production and purification of tick salivary serpins in bacterial expression system - Röhrnbacher, Simone (Jihočeská univerzita, 2018)
The aim of this thesis was to produce several tick salivary serine protease inhibitors and a chimeric mouse-tick serpin in a bacterial expression system, to refold and purify the proteins and to finally test them in protease inhibitor assays for drawing early conclusions about their function in tick-host interactions.
The production and purification of tick salivary serpins in bacterial expression system